The multichannel experimental and theoretical study of the 12C(18O,18F)12B single charge exchange reaction mechanism - Spatafora Alessandro; Carbone Diana; Cappuzzello Francesco; Cavallaro Manuela; Acosta Luis E.; Agodi Clementina; Amador-Valenzuela Paulina; Borello-Lewin Thereza; Brischetto Giuseppe A.; Calvo Daniela; Chávez-Lomelí Efrain R.; Ciraldo Irene; et al. (EPJ Web of Conferences, 2024)
The study of a network of nuclear reactions populated in the 18O + 12C collision is the main topic of the present paper. It was performed to test nuclear structure and reaction theories in describing the full reaction mechanism occurring in the (18O, 18F) single charge exchange nuclear reaction. From the experimental side, an 18O beam was produced at 275 MeV incident energy by the K800 superconducting cyclotron and the MAGNEX magnetic spectrometer was used at the Laboratori Nazionali del Sud of the Istituto Nazionale di Fisica Nucleare to momentum analyse the ejectiles produced in the nuclear reactions within the same experimental setup. From the theoretical side, the proposed approach consists of analysing the whole network of nuclear reactions in the framework of a unique comprehensive and coherent theoretical calculation. This holistic approach, applied both to the experimental and theoretical analysis, is the main feature and novelty of the work presented here.